Injuries of Kaplan fibers in ACL deficient and reconstructed knees – redefining the structure and risk assessment on MRI using injury patterns. Issue 6 (30th June 2021) - Iordache, Edna A.; Hirschmann, Michael T.; Amsler, Felix; Yang, Schu-Ren; Hess, Silvan; Hirschmann, Anna
Objectives: To determine an injury pattern of knee structures along torn Kaplan fibers in ACL deficient knees and to observe the healing process of Kaplan fibers in ACL reconstructed knees. Methods: A total of 101 knee MRIs obtained between January 2004 and April 2020 with full-thickness ACL tears were retrospectively assessed for visibility and impairment of three Kaplan bundles (proximal, distal and epicondylar band) and for associated injuries by two fellowship-trained independent musculoskeletal radiologists. A subgroup of 33 follow-up knee MRIs after ACL reconstruction was assessed to observe the natural evolution of Kaplan fibers injury. Descriptive statistics and Spearman correlation coefficients (P<.05) were used to determine injury patterns. Results: Kaplan fibers were injured in 43 of 101 (43%) acute ACL deficient knees. Proximal Kaplan fibers were visible in less than 48 of 101 (50%) knees as opposed to the distal Kaplan fibers and epicondylar Kaplan band which were both visible in 98 of 101 (97%) knees. Injury to the Kaplan complex was significantly associated with anterolateral (rho, 0.36; P<.001) and lateral collateral ligament impairment (rho, 0.21;P<.05) and medial femoral bone marrow edema (rho, 0.21;P<.05). After ACL reconstruction, only two of 33 (6%) patients showed torn Kaplan and 13 of 33 (39%) distal Kaplan fibers were scarred. Conclusion: Torn Kaplan fibers are associated with anterolateral and lateral collateral ligament injuries in ACL deficiency, indicating a more severe anterolateral and rotatory instability. Injury patterns in ACL deficient knees can eliminate the uncertainty of proximal Kaplan fibers identification. Kaplan fiber tears tend to heal following ACL reconstruction.